Powerboat Care and Repair : How to Keep Your Outboard, Sterndrive, or Gas-Inboard Boat Alive and Well - Berrien Allen (International Marinne, 2003)
The boat-maintenance bible for small powerboats, Powerboat Care and Repair covers all you need to know to keep your boat running and looking like a million bucks. You'll find step-by-step guidance on: